(untitled) - Moore, David S. (New York, 1989)
The purpose of this study guide is to guide your learning of basic statistics. The study guide links the television programs in "Against All Odds: Inside Statistics" with the telecourse text, "Introduction to the Practice of Statistics" by David S. Moore and george P. McCabe. The study guide would help anyone studying statistics understand the subject, as it breaks statistics into units with learning objectives and reading assignments, plus a problem assignment and self-test questions with fully worked solutions.
Keywords: Mathematical statistics,Toán thống kê